2020
DOI: 10.5713/ajas.19.0471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial additive on microbial populations, ensiling characteristics, and spoilage loss of delayed sealing silage of Napier grass

Abstract: Objective: To measure whether a microbial additive could effectively improve the fermentation quality of delayed-sealing (DS) silage, we studied the effects of inoculants of lactic acid bacteria (LAB) and cellulase enzyme on microbial populations, ensiling characteristics, and spoilage loss of DS silage of Napier grass in Africa.Methods: Quick-sealing (QS) and DS silages were prepared with and without LAB (Lactobacillus plantarum) inoculant, cellulase enzymes, and their combination. The QS material was directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…However, due to the low water content, low water soluble carbohydrate, low lactic acid bacteria attachment, and high buffer energy of natural forage, direct silage is difficult to succeed ( Zhang et al, 2016 ; Hou et al, 2017 ). To solve this problem, Cai et al (2020) evaluated the effects of additives on native grass silage and found that the use of L and cellulase can improve the fermentation quality of native grass silage. L is the most common type of silage additive, capable of ensuring extensive fermentation and efficient substrate utilization in ensiled materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low water content, low water soluble carbohydrate, low lactic acid bacteria attachment, and high buffer energy of natural forage, direct silage is difficult to succeed ( Zhang et al, 2016 ; Hou et al, 2017 ). To solve this problem, Cai et al (2020) evaluated the effects of additives on native grass silage and found that the use of L and cellulase can improve the fermentation quality of native grass silage. L is the most common type of silage additive, capable of ensuring extensive fermentation and efficient substrate utilization in ensiled materials.…”
Section: Introductionmentioning
confidence: 99%
“…proved to be an appropriate method for Napier grass preservation post-harvest [1,2]. Napier grass has a dry matter biomass productivity of ~ 40 ton per hectare per year according to Li et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Southern China, especially Guangdong province, haymaking is restricted by unfavorable climatic conditions (high air moisture content, local precipitation, etc.). Consequently, ensiling has been widely proved to be an appropriate method for Napier grass preservation post-harvest [ 1 , 2 ]. Napier grass has a dry matter (DM) biomass productivity of ~40 ton per hectare per year according to Li et al [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of defective bananas in this experiment was as high as 75%, which exceeded the ideal range of 60-70% moisture content for silage preparation. In addition, the number of epiphytic LAB showed a level of 103 CFU/g of FM, which was lower than the basic bacteria number 105 required for high-quality silage preparation [31,32]. When LAB fail to produce sufficient lactic acid during fermentation to reduce the pH and inhibit the growth of harmful bacteria, the resulting silage will be of poor quality.…”
Section: Discussionmentioning
confidence: 92%